A Coupled Biomechanical-Smoothed Particle Hydrodynamics Model for Horse Racing Tracks - Harrison, Simon M.; Whitton, R. Chris; Stover, Susan M.; Symons, Jennifer E.; Cleary, Paul W. (Frontiers in Bioengineering and Biotechnology, 2022)
Distal limb injuries are common in racing horses and track surface properties are statistically associated with injury risk. To better understand how track surfaces may contribute to equine limb injury, we developed the first 3D computational model of the equine hoof interacting with a racetrack and simulated interactions with model representations of (1) a dirt surface and (2) an all-weather synthetic track. First, a computational track model using the Smoothed Particle Hydrodynamics (SPH) method with a Drucker-Prager (D-P) elastoplastic material model was developed. It was validated against analytical models and published data and then calibrated using results of a custom track testing device applied to the two racetrack types. Second, a sensitivity analysis was performed to determine which model parameters contribute most significantly to the mechanical response of the track under impact-type loading. Third, the SPH track model was coupled to a biomechanical model of the horse forelimb and applied to hoof-track impact for a horse galloping on each track surface. We found that (a) the SPH track model was well validated and it could be calibrated to accurately represent impact loading of racetrack surfaces at two angles of impact; (b) the amount of harrowing applied to the track had the largest effect on impact loading, followed by elastic modulus and yield stress; (c) the model is able to accurately simulate hoof-ground interaction and enables study of the relationship between track surface parameters and the loading on horses’ distal forelimbs.